Hybrid Solar Absorber–Emitter by Coherence‐Enhanced Absorption for Improved Solar Thermophotovoltaic Conversion. Issue 24 (23rd October 2018) - Wang, Yang; Zhou, Lin; Zhang, Ye; Yu, Jianyu; Huang, Baili; Wang, Yuxi; Lai, Yun; Zhu, Shining; Zhu, Jia
Abstract: Spectrum selective absorbers and emitters, with advantages of high temperature tolerance, wide angle insensitivity, and scalable fabrication processes, are crucial components for solar thermophotovoltaics (STPV). A bifunctional hybrid absorber–emitter (HAE) for efficient STPV by sequentially depositing HfO2 /Mo/HfO2 films on a metallic surface is demonstrated here. Simultaneous broadband solar absorption and narrowband infrared emission are enabled by the same surface of the structure. By fine steering coherent perfect absorption of the ultrathin Mo film and destructive interference of interfacial reflections across the top HfO2 layer, the HAE exhibits a measured emissivity of 0.97 at 1.8 µm as well as an average absorptivity of ≈80% over 400–1000 nm, respectively, both of which are well maintained under nearly omnidirectional irradiance (≈80°) and up to 1373 K thermal stability test. The features of multiple coherence‐enhanced all‐in‐one single‐surface HAE (dual‐spectrum selectivity, wide angle tolerance, high temperature stability, etc.), make the HAE a good candidate for specialized efficient STPV. As a demonstration, it is theoretically shown that the HAE‐based cage‐type STPV can enable a maximal system efficiency increment of >15% compared to the double‐side planar systems, providing a potential route leading to integrated STPV–TPV systems for all‐climate operation in future. Abstract : A hybrid solar absorber and thermal emitter (HAE) is constructed on one material surface, based on multiple coherence‐enhanced absorption. The advantages of a wide angle tolerance and high temperature stability make the HAE a good candidate for specialized solar thermophotovoltaics (STPV) – like cage‐type systems with a suppressed radiation loss compared to double‐side planar systems, providing potential routes to integrated STPV–TPV for all‐climate operation.